The gynoecium structure in Dracaena fragrans (L.) Ker Gawl., Sansevieria parva N.E. Brown and S. trifasciata Prain (Asparagaceae) with special emphasis on the structure of the septal nectary - Одінцова, Анастасія Валеріївна; Фіщук, Оксана Сергіївна; Odintsova, Anastasiia V.; Fishchuk, Oksana S.; Sulborska, Aneta (Polish Botanical Society, 2013)
In the gynoecium of Dracaena fragrans, Sansevieria parva and S. trifasciata, the vertical zonality of the ovary, the structural zonality of the gynoecium following Leinfellner, and the zonality of the septal nectary were studied. The ovary structure is characterised by a high parenchymatous ovary base and ovary roof as well as a long septal nectary that can be extended in both of them and opens with secretory nectary splits. The gynoecium of these species has a short synascidiate zone, a fertile hemisynascidiate zone with a median ovule attached, a hemisymlicate zone (only in D. fragrans) and an asymplicate zone (with postgenitally fused carpels) that comprises the ovary roof, common style and stigma. In the septal nectary, we detected three vertical zones: the basal zone of the distinct nectary in the ovary base or/and the synascidiate zone, the zone of the common nectary (in the hemisynascidiate and hemisymlicate zones) and the zone of the external nectary (the nectary splits in the asymplicate zone). The gynoecium structure in the studied species shows differences in the length of the gynoecium and septal nectary zones and also in the interrelationships of all these three types of vertical zonality.
Keywords: Dracaena; Sansevieria; gynoecium morphology; gynoecium vertical zonality; ovary structure; septal nectary zonality